Analysis of Flood Disaster Mitigation Through Spatial and Environmental Policies for Flood Management in Bekasi City, West Java - Suprapti Widiasih; Faizah Julina; Sri Susanti Widyasari (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2026)
This study aims to analyze the effectiveness of the implementation of spatial and environmental policies in flood mitigation in Bekasi City and identify the main supporting and inhibiting factors. The city of Bekasi as part of the Greater Jakarta metropolitan area faces an increased risk of flooding due to urbanization, land conversion, and weak spatial control. This study uses a descriptive qualitative approach with in-depth interview techniques and Focus Group Discussion (FGD) with stakeholders, including DLH, PUPR, BPBD, Bappeda, WALHI, and community representatives in flood-prone areas. Data analysis was carried out using NVivo software through open coding stages, thematic categorization, and frequency analysis to identify dominant issues based on Mazmanian and Sabatier policy implementation models. The results of the thematic analysis identified seven main themes, namely policies and regulations (85), institutional capacity (78), coordination and collaboration (82), resources and infrastructure (74), community participation (69), challenges and obstacles (62), and recommendations for improvement (88). The findings show that the main obstacles lie in weak regulatory enforcement, sub-optimal cross-sectoral coordination, and limited resources and technical capacity. This study concludes that effective flood mitigation requires strengthening collaborative governance, risk-based policy integration, and the development of green and blue infrastructure and integrated disaster information systems. This study makes a theoretical contribution to the study of public policy implementation and practical recommendations for strengthening urban resilience to flood risk.